OsEUL Lectin Gene Expression in Rice: Stress Regulation, Subcellular Localization and Tissue Specificity - Lambin, Jeroen; Demirel Asci, Sinem; Dubiel, Malgorzata; Tsaneva, Mariya; Verbeke, Isabel; Wytynck, Pieter; De Zaeytijd, Jeroen; Smagghe, Guy; Subramanyam, Kondeti; Van Damme, Els J. M. (Frontiers in Plant Science, 2020)
The Euonymus lectin (EUL) family is a unique group of carbohydrate-binding proteins that is omnipresent in plants. Sequences encoding EUL-related lectins have been retrieved from all completely sequenced plant genomes. The rice (Oryza sativa) genome contains 5 functional EUL genes referred to as OsEULS2, OsEULS3, OsEULD1a, OsEULD1b and OsEULD2. In this study we focused on the tissue specific expression, stress inducibility and subcellular localization of the rice EULs. Even though the EUL domain sequence is highly conserved among the rice EULs (at least 80% sequence similarity) different biotic and abiotic stress treatments yielded unique responses for the different EULs. Transcript levels for OsEULs were differentially affected by drought and salt stress, ABA treatment, pathogen infection or insect infestation. Analysis of promoter activity revealed differential expression and tissue specificity for the 5 OsEUL genes, with most expression observed in the vascular system of roots and shoots, as well as in the root tips and seeds. At cell level, all OsEULs are located in the nucleus whereas OsEULD1b and OsEULD2 also locate to the cytoplasm. This paper contributes to the functional characterization of the EULs and provides insight in the biological importance of this family of proteins for rice.